CYTOPROTECTIVE AND DIPEPTIDYL PEPTIDASE IV (DPP-IV/CD26) INHIBITORY ROLES OF OCIMUM SANCTUM AND MOMORDICA CHARANTIA EXTRACT - SINGH, ANAND KRISHNA; JATWA, RAMESHWAR; JOSHI, JAYA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective- The present work deals with investigation of DPP-IV inhibition activity vis a vis cytoprotective potential, if any, in two ant-diabetic plants in methanolic extracts of Ocimum sanctum (Tulsi) leaves and. Momordica charantia (Karela/ bitter melon) fruit. Methods- The DPP-IV activity and cytoprotective were studied based on different antioxidant activity assays such as hepatic lipid per- oxidation, erythrocytes haemolysis inhibition, in vitro DPP-IV activity; DPPH radical scavenging efficacy; ferric reducing potential; reducing power and total phenolic contents at the varying concentrations in the extracts of O.sanctum and M.charantia. Result- Methanolic extract (0.5 mg/ml) of OS inhibited DPP-IV activities (66.81±0.05percent) at greater extent than that of M. charantia (53.25±0.04percent); O .sanctum extract contains relatively higher amount of total phenolic content, elevated DPPH free radical scavenging potential and pronounced reducing power efficacy than that of M. charantia. O .sanctum inhibited erythrocytes haemolysis at greater extent (13.1±0.188 µg/ml) as compared to M. charantia (10.3±0.41 µg/ml). Conclusion- The result of present study ravel that O .sanctum and M. charantia extracts contain some novel DPP-IV inhibitors with antiperoxidative potential and could be developed as therapeutic molecules for type 2 diabetes mellitus. Key words: Ant-diabetic plants; Antioxidant; DPP-IV inhibitors; In vitro; Type 2 diabetes mellitus